Exergetic Assessment of Waste Gas to Energy in a Novel Integrated NGL Recovery and Power Generation Plant - Aigba, Peter Alenoghena; Emovon, Ikuobase; Samuel, Olusegun David; Chintua Enweremadu, Christopher; Abdeljawad, Thabet; Al-Mdallal, Qasem M.; Afzal, Asif (Frontiers in Energy Research, 2022)
Natural gas processing, as one of the major energy sources, has become a focal point in boosting the energy value chain by processing high commercial value products such as natural gas liquefied (NGL), condensate, gas to liquid (GTL), and electricity generation, as well as amplifying its usefulness to human well-being and global prosperity. Despite advances in waste gas management technology, various obstacles remain in the way of complete removal of emissions into the environment, ranging from greater releases to a lack of motivation to reach an evolutionary commercialization scale. This research describes a unique integrated system that produces NGL and electricity by processing and recovering energy from waste gas. Exergetic analysis has been offered as a tool to identify causes of thermodynamic irreversibilities in an integrated plant while simultaneously looking for solutions to improve the process. The recovery of 60 kBD NGL and 2.6 kg.mol/s of lean (methane) gas as residue was validated in this study, which processed 320 MMSCFD of waste gas. The residue lean gas is then combusted to generate steam, which is used to energize a steam power plant that generates 646 MW of electricity. This energy conversion (fossil fuel) process results in the emission of pollutants that affect the ecosystems. As a result, this study aims to eliminate component inefficiencies in natural gas use to reduce greenhouse gas (GHG) emissions and other pollutants. To assess the feasibility of this concept, multiple simulation models were built using the AspenOne Hysys v10 and Aspen Plus v10 simulation tools. Despite the inefficiencies identified in the gas-to-gas process heat exchangers in the NGL recovery plant, analysis revealed that about 1.5% of exergy was lost from the demethanizer column. Similarly, 1.4% exergy loss to the environment was found on the steam power plant side, with the heat recovery steam generator (HRSG) and the combustion chambers causing the most exergy destruction. This integrated plant system, on the other hand, has been discovered to be not only a lucrative alternative to waste gas management, but also a “flare-capture” option for emission and (GHG) reduction, as well as waste gas to energy optimization.